TRANSLATION ANALYSIS OF RESPOND-TO-REQUEST IN 'THE LOST HERO' AND 'THE SON OF NEPTUNE' NOVELS - Dewinta Khoirul Anis (Leksema: Jurnal Bahasa dan Sastra, 2019)
This research aims to analyze the translation techniques used and assess the translation quality in the form of accuracy and acceptability assessment on respond-to-request speech acts of The Lost Hero and The Son of Neptune novel series written by Rick Riordan. This research used a qualitative-descriptive method whose data sources were the novel series and two raters who had aptitudes in assessing translation quality. The methods to collect and analyze the data were content analysis and Focus Group Discussion. The study found 11 translation techniques applied in translating the respond-to-request speech acts. They were establish equivalent, variation, borrowing, modulation, amplification, adaptation, discursive creation, transposition, reduction, literal translation, and substitution. Dealing with the quality, the findings showed that most translations were accurate and acceptable. The majority of accurate translations used established equivalent technique. The less accurate translations applied modulation, amplification addition, discursive creation, literal translation and reduction whereas the inaccurate ones applied literal translation technique. Meanwhile, the majority of acceptable translations used establish equivalent and he less acceptable translations applied modulation, amplification addition, and discursive creation. Thus, this research proposes that the use of appropriate translation techniques is very important for the results of quality translation that is easily understood by the reader.